2016
DOI: 10.1021/acs.bioconjchem.5b00608
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Peptide Conjugation Enhances the Activity of Peroxidase-Mimicking DNAzymes

Abstract: Peroxidase-mimicking DNAzymes containing G-quadruplex structures are widely applied in chemistry as catalysts and signal amplification for biosensing. Enhancing the catalytic activity of these DNAzymes can therefore improve the performance of many catalysts and biosensors using them. In this work, we synthesized cationic peptide conjugates of peroxidase-mimicking DNAzymes, which were found to exhibit both enhanced peroxidase and oxidase activities up to 4-fold and 3-fold compared with the original DNAzymes, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 75 publications
1
16
0
Order By: Relevance
“…Similar rate-enhancements were observed by the addition of the nucleotide ATP to DNAzyme reactions [12,13]. It has also been reported that the conjugation of hemin with the G4-quadruplex moiety via covalent linkage [14] or with cationic peptides [15] can enhance the activities of DNAzymes. Other studies have focused on the rate-enhancing effects of flanking adenine or cytosine nucleotides on G-quadruplex activities [16][17][18][19].…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Similar rate-enhancements were observed by the addition of the nucleotide ATP to DNAzyme reactions [12,13]. It has also been reported that the conjugation of hemin with the G4-quadruplex moiety via covalent linkage [14] or with cationic peptides [15] can enhance the activities of DNAzymes. Other studies have focused on the rate-enhancing effects of flanking adenine or cytosine nucleotides on G-quadruplex activities [16][17][18][19].…”
Section: Introductionsupporting
confidence: 70%
“…The absorbance intensity at λ = 415 nm (corresponding to the amount of ABTS • formed) was measured as a function of time. The initial rates (V o ) were calculated from the slope of the initial (30 s) linear portion of the increase in absorbance [15,39].…”
Section: Determination Of G4/hemin Dnazyme Activitymentioning
confidence: 99%
“…This intermediate finally withdraws one electron from another ABTS molecule to provide the initial porph⋅Fe III cofactor. Upon addition of H 2 O 2 , the dynamics of the absorbance change at 404 nm demonstrated a fast degradation tendency within five minutes (Supporting Information, Figure S11), while G4, G5, and G6 DNAzyme were characterized by the low degradation rates (Figure B). Interestingly, G4A and AG4A DNAzyme showed similar degradation rates, which were higher than those of G4 modified at 5′ and/or 3′ ends with dT or dC.…”
Section: Figurementioning
confidence: 99%
“…G-quadruplex/hemin complexesc an catalyze the oxidation of substrates (2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonica cid) (ABTS),3 ,3',5,5'-tetramethylbenzidine (TMB), or luminol) in the presence of H 2 O 2 ,a nd the subsequentc olor change (ABTS, l max = 415 nm when oxidized) has been used in colorimetric and/or chemiluminescent detection of various targets.C ompared with proteinous enzymes, G-quadruplex/hemin DNAzymes have many advantages. Smallm olecule additives (ATP or spermine), [13][14][15] may be added to the G-quadruplex/hemin system;a lternatively, covalent conjugation of ac ationicp eptide [16] or hemin to G-quadruplex, [17] or chemical modification of G-quadruplexes [18] have been used. Furthermore, it is asimple and sensitive biosensor and molecular machine that is suitable for the detection of multiple targets such as metal ions, [3] small molecules, [4] and biomolecules (DNA and proteins), [5,6] which were described in recent reviews.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] To enhance the performance and activity of peroxidase-mimicking DNAzymes, different strategies have been proposed. Smallm olecule additives (ATP or spermine), [13][14][15] may be added to the G-quadruplex/hemin system;a lternatively, covalent conjugation of ac ationicp eptide [16] or hemin to G-quadruplex, [17] or chemical modification of G-quadruplexes [18] have been used. Recently,f lankings equences such as d(CCC) [19] and dA, [20] in intramolecular parallel G-quadruplexes, were found to enhance the activity of G-quadruplex/hemin DNAzymes.…”
Section: Introductionmentioning
confidence: 99%